The Influence of Da'wah Messages on the Ustadz Adi Hidayat Official YouTube Account on Students' Religious Behavior - M. Fadhli; Nashrillah Nashrillah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The phenomenon of the development of digital da'wah through YouTube has become an effective means of conveying Islamic values to the younger generation, where university students play a strategic role in critically and objectively assessing the effectiveness of online da'wah. This study examines the influence of da'wah messages delivered through the Ustadz Adi Hidayat Official YouTube channel on the religious behavior of students at the Universitas Islam Negeri Sumatera Utara Medan. This research employs a quantitative method with a correlational approach. Data were collected through questionnaires distributed to 100 students selected using purposive sampling. The validity and reliability of the research instruments were tested using SPSS software. Hypothesis testing was conducted using simple linear regression, specifically the t-test. The results show a significant positive influence of the da'wah messages on the Ustadz Adi Hidayat Official YouTube channel on students' religious behavior. The coefficient of determination (R²) of 0.435 indicates that 43.5% of the students' religious behavior can be explained by the da'wah message variable. The significance value of 0.000 (< 0.05) indicates the relationship is statistically significant. Conclusion: The digital da'wah content on the official YouTube channel of the Ustadz Adi Hidayat significantly contributes to increasing students' religiosity.